Mother's knowledge about pre-school child's oral health - Suresh, B S; Ravishankar, T L; Chaitra, T R; Mohapatra, A K; Gupta, V (Journal of the Indian Society of Pedodontics and Preventive Dentistry, 2010)
Children under the age of 5 years generally spend most of their time with their parents and guardians, especially mothers, even when they attend pre-schools or nurseries. It has been found that young children's oral health maintenance and outcomes are influenced by their parent's knowledge and beliefs. This study was done to assess the mother's knowledge about the oral health of their pre-school children in Moradabad, India. Mothers of children aged 1-4 years, attending the hospital for vaccination or regular checkups in the pediatric division of government hospitals, were invited to participate in the study. A 20-item questionnaire covering socio-demographic characteristics, dietary practices, oral hygiene practices and importance of deciduous teeth, was distributed to their mothers, during their visit to the hospital. Responses of the mothers were recorded on a Likert Scale. The sample comprised 406 mothers, with the mean age of children being 3.8 years. Three hundred (73.8%) mothers had a good knowledge about diet and dietary practices, while only 110 (27.1%) and 103 (25.4%) mothers were found to have a good knowledge about the importance of oral hygiene practices and importance of deciduous teeth, respectively. Mothers with higher educational qualification and information gained through dentist had a better knowledge about child's oral health. Oral hygiene habits and dietary habits are established during pre-school days and the parents, especially mothers, function as role models for their children.